”RUWATAN”: REKONSILIASI KOSMIS? Refleksi Teologis atas Usaha Menginkulturasikan Upacara ”Ruwatan” - Petrus Maria Handoko (Litbang STFT Widya Sasana Malang, 2006)
There are numerous version of stories of Batara Kala and Ruwatan. Principally Batara Kala is a personification of evil presented in form of myth. Sukerta is the food-victim of Batara Kala, which is determined by a given situation. Therefore, Ruwatan is a rite of purification or exorcism. Seen as such, the myth of Batara Kala can be paralled with the idea of the objectification process of sin into a structure which is mentioned by the Post-synodal Apostolic Exhortation Reconciliatio et Paenitentia. This concept of social sin does not liberate, rather emphasizes personal responsibility of sin. It calls for an acknowledgment that every sin has direct implications to nature. Ruwatan is an expression of deepest longing of man for a new earth and a new heaven. It is a cosmic reconciliation. The Eucharist is a summit expression of this cosmic reconcilition.